Comparative Analysis of Lower Gastrointestinal Bleeding Due to Diverticular Disease Versus Other Etiologies - Chiquetti, Camila Vieira; dos Santos, Carlos Henrique Marques; Zeferino, Bárbara Érnica; Ribeiro, Carlos Otávio da Silva; Fonseca, Odinilson Almeida (Journal of Coloproctology, 2025)
Lower gastrointestinal bleeding (LGIB) is defined as bleeding located below the ligament of Treitz, with colonic diverticular disease (CDD) being the main etiology. Characteristics of LGIB caused by CDD were compared with other etiologies to establish the main differences.This observational, analytical, and prospective study included individuals with signs suggestive of LGIB, after excluding upper gastrointestinal bleeding via endoscopy. Data were recorded during clinical follow-up from March 2023 to December 2024. A significant level of 5% was considered.A total of 108 patients was evaluated. The main etiologies were CDD (54.6% - n = 59), hemorrhoidal disease (11.1% - n = 12), angiodysplasia (10.2% - n = 11), and neoplasia (10.2% - n = 11). A significant association was found between CDD and patients over 60 years old (p = 0.035). Patients with CDD sought medical care within two days (p = 0.012), while those in the group with HD, angiodysplasia, and neoplasia sought care after seven days (p = 0.012). Among the patients with CDD, 96.1% were treated clinically, while 65.3% of patients with HD, angiodysplasia, or neoplasia required surgical or endoscopic treatment. HD, angiodysplasia, and neoplasia showed a higher prevalence of hematochezia (58.8%), while CDD showed a higher prevalence of enterorrhagia (71.9%) (p < 0.05).CDD is the leading cause of LGIB, typically presenting with self-limited bleeding and associated with enterorrhagia. Other causes include hemorrhoidal disease, angiodysplasia, and neoplasms, which often require endoscopic or surgical intervention and present as hematochezia. No significant differences were observed between groups regarding sex, ethnicity, and comorbidities.
Keywords: gastrointestinal hemorrhage; diverticular diseases; hemorrhage